Modular system of culturing mixed-sex Java tilapia, Oreochromis mossambicus in brackishwater fishpond at two stocking densities - Silva, Alberto Alfar (College of Fisheries, University of the Philippines in the Visayas, 1993)
Two experimental culture systems for Java tilapia, namely : modular system with two stocking densities of 6, 667/ha and 13,334/ha, Treatments I and III, respectively, and straight culture system also with two stocking densities of 6,667/ha and 13,334/ha Treatments II and IV, respectively, were tested to determine their effects on the growth and survival of mixed-sex Java Tilapia in 16 units of 450 sq m ponds of the Iloilo State College of Fisheries, Barotac Nuevo, Iloilo. The experiment was conducted using a factorial in a completely randomized design (CRD) and replicated four tmes for a period of 86 days. Average initial weight of the experimental fish ranged from 28.67g to 31.46g. Highest mean weight for tilapia at harvest was obtained in Treatment I (56.13g). Mean weights of tilapia for treatments II, III, and IV were 47.63g, 51.31g, and 49.48g, respectively. The effect of treatmets in mean weight at harvest were not significantly different (P> 0.05). The mean rate of survival did not differ significantly among Treatments. Highest survival was obtained in Treatment I (85.33%) while Treatment IV gave the lowest survival of 77.58%. In terms of tilapia young production (kg/ha) at harvest, the modular ponds (treatments I and III) differ significantly from the straight-culture system (Treatments II and IV). There ws no significant difference between Treatment I (23.22 kg/ha) and Treatment III (32.97 kg/ha) while Treatment II (250.51 kg/ha) differed significantly from Treatment IV (177.43 kg/ha) at 5% level of significance. Meanwhile, aveerage number of tilapia young assessed at transfer in modular ponds was obviously higher in Treatment III (22.448 kg/ha) from Treatment I (15,264/ha). Profitwise, Treatment III gave the highest return of investment and cost-benefit ratio of 59.52% and 1.59, respectively, which indicated the advantage of using modular system with higher stocking density as one of the best culture systems of culturing mixed-sex Java Tilapia.